Restoration of Cerebral and Systemic Microvascular Architecture in APP/PS1 Transgenic Mice Following Treatment with Liraglutide™. (February 2015) - Kelly, Patricia; McClean, Paula L.; Ackermann, Maximilian; Konerding, Moritz A.; Hölscher, Christian; Mitchell, Christopher A.
Abstract Objective Cerebral microvascular impairments occurring in AD may reduce Aβ peptide clearance and impact upon circulatory ultrastructure and function. We hypothesized that microvascular pathologies occur in organs responsible for systemic Aβ peptide clearance in a model of AD and that Liraglutide (Victoza®) improves vessel architecture. Methods Seven‐month‐old APP/PS1 and age‐matched wild‐type mice received once‐daily intraperitoneal injections of either Liraglutide or saline (n = 4 per group) for eight weeks. Casts of cerebral, splenic, hepatic, and renal microanatomy were analyzed using SEM. Results Casts from wild‐type mice showed regularly spaced microvasculature with smooth lumenal profiles, whereas APP/PS1 mice revealed evidence of microangiopathies including cerebral microanuerysms, intracerebral microvascular leakage, extravasation from renal glomerular microvessels, and significant reductions in both splenic sinus density (p = 0.0286) and intussusceptive microvascular pillars (p = 0.0412). Quantification of hepatic vascular ultrastructure in APP/PS1 mice revealed that vessel parameters (width, length, branching points, intussusceptive pillars and microaneurysms) were not significantly different from wild‐type mice. Systemic administration of Liraglutide reduced the incidence of cerebral microanuerysms and leakage, restored renal microvascular architecture and significantly increased both splenic venous sinus number (p = 0.0286) and intussusceptive pillar formation (p = 0.0129). Conclusion Liraglutide restores cerebral, splenic, and renal architecture in APP/PS1 mice.